Management of acute pancreatitis (AP) – Polish Pancreatic Club recommendations - Rosołowski, Mariusz; Lipiński, Michał; Dobosz, Marek; Durlik, Marek; Głuszek, Stanisław; Kuśnierz, Katarzyna; Lampe, Paweł; Małecka-Panas, Ewa; Nowakowska-Duława, Ewa; Nowak-Niezgoda, Magdalena; Radomańska, Barbara; Talar-Wojnarowska, Renata; et al. (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
The presented recommendations concern the current management of acute pancreatitis. The recommendations relate to the diagnostics and treatment of early and late phases of acute pancreatitis and complications of the disease taking into consideration surgical and endoscopic methods. All the recommendations were subjected to voting by the members of the Working Group of the Polish Pancreatic Club, who evaluated them every single time on a five-point scale, where A means full acceptance, B means acceptance with a certain reservation, C means acceptance with a serious reservation, D means rejection with a certain reservation and E means full rejection. The results of the vote, together with commentary, are provided for each recommendation.